Quranic Interpretation Of Halal Food and Its Implementation In The Economic Development Of Sharia - Nasrudin, Nasrudin; Ruhendi, Ateng; Nursari, Nina; Jamaludin, Jujun (STAI Siliwangi Bandung, 2023)
Abstract: This study aims to analyze the role of halal food described in the Quran for the fulfillment of basic human needs which ultimately intersect with economic activities, one of which is in the development of the sharia economy. This research uses a descriptive qualitative approach, with a review of documents. The results of this paper are more focused on the interpretation of Q.S. al-Baqarah Verse 168 and al-Maidah Verse 88 in the tafsir al-Maraghy and al-Misbah. So that in the explanation describes the extent to which the implementation of this verse can move humans in conducting the economy based on the teachings practiced by the Prophet SAW, especially those related to the development of the sharia economy.Keywords: sharia economics, halal food, qur'anic interpretation Abstrak: Penelitian ini bertujuan untuk menganalisis peran makanan halal yang dijabarkan dalam al-Quran untuk pemenuhan kebutuhan pokok manusia yang pada akhirnya bersinggungan dengan kegiatan ekonomi, salah satunya dalam pengembangan ekonomi syariah. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan penelaahan dokumen. Hasil penelitian dari tulisan ini lebih difokuskan pada penafsiran Q.S. al-Baqarah Ayat 168 dan al-Maidah Ayat 88 dalam tafsir al-Maraghy dan al-Misbah. Sehingga dalam penjelasannya menjabarkan sejauh mana implementasi ayat ini dapat menggerakkan manusia dalam melakukan perekonomian dengan berlandaskan ajaran yang dipraktikkan oleh Rasulullah SAW terutama yang berhubungan dengan pengembangan ekonomi syariah.